Reversible facile Rb+ and K+ ions de/insertion in a KTiOPO4-type RbVPO4F cathode material. Issue 29 (12th July 2018) - Fedotov, Stanislav S.; Samarin, Aleksandr Sh.; Nikitina, Victoria A.; Aksyonov, Dmitry A.; Sokolov, Sergey A.; Zhugayevych, Andriy; Stevenson, Keith J.; Khasanova, Nellie R.; Abakumov, Artem M.; Antipov, Evgeny V.
Abstract : In this paper, we report on a novel RbVPO4 F fluoride phosphate, which adopts the KTiOPO4 (KTP) type structure and complements the AVPO4 F (A = alkali metal) family of positive electrode (cathode) materials for metal-ion batteries. Abstract : In this paper, we report on a novel RbVPO4 F fluoride phosphate, which adopts the KTiOPO4 (KTP) type structure and complements the AVPO4 F (A = alkali metal) family of positive electrode (cathode) materials for metal-ion batteries. RbVPO4 F was synthesized via a freeze-drying assisted solid-state route and characterized via structural, computational and electrochemical methods. RbVPO4 F represents the first example of reversible electrochemical Rb + de/insertion in a crystalline oxypolyanionic framework. The electrochemical measurements on RbVPO4 F in a three-electrode cell configuration in RbClO4 -saturated propylene carbonate (PC) electrolyte revealed that the material exhibits reversible Rb + de/insertion within the 0.4–1.3 V vs. Ag + /Ag potential range (∼3.9–4.8 V vs. K + /K) displaying rather high diffusion coefficients of (0.3–1.0) × 10 −11 cm 2 s −1 comparable to those of K + in KVPO4 F that supports reasonably fast ionic mobility in the KTP structure despite the large ionic radius of the Rb + ions. The energy barriers of Rb + ion transport are exceptionally low not exceeding 0.2 eV along the c -axis and correlating well with diffusion coefficients estimated using the DFT+U-NEB methodology and with the experimentally determined transport properties. These results suggest a new paradigm for the development of materials that support many monovalent ion reversible de/insertion processes in a single prototypical structural oxypolyanionic framework.